A Study On Protocol Stack In 6lowpan Model - Ismail, Nurul Halimatul Asmak; Hassan, Rosilah; Wan Mohd Ghazali, Khadijah (Little Lion Scientific Islamabad Pakistan, 2012)
Due to recent advances of heterogeneous network and the emergence of Internet of Things (IoT), wireless personal area networks including wireless sensor networks are assumed to be part of the huge heterogeneous network. This calls for a smooth integration between the higher network layer protocols Internet Protocol version 6 (IPv6) and the lower media access control (MAC) layer protocol IEEE 802.15.4. IEEE 802.15.4 is a standard that specifies the physical layer and MAC layer for Wireless Personal Area Network (WPAN). This standard is suited for Low-Rate Wireless Personal Area Networks (LR-WPANs), a constrained network of tiny, low power, low rate, small size memory with low computation and communication capabilities. However, IPv6 is forming the backbone of the desired heterogeneous network. Direct integration between IPv6 and IEEE 802.15.4 lower network layers is not possible. Hence, latest technology development is the transmission of IPv6 packets over Low-power Wireless Personal Area Networks (6LoWPAN). This has enforced some modification to the existing protocol stack and introduced the 6LoWPAN protocol stack. The 6LoWPAN protocol stack involves 802.15.4 physical (PHY) and Medium Access Control (MAC) layer, 6LoWPAN adaptation layer, network layer, transport layer and application layer with specific 6LoWPAN application. This review paper describes all layers in 6LoWPAN protocol stack including its routing protocols, namely the Route-over and Mesh-under. These routing schemes are applied in 6LoWPAN adaptation layer and network layer.